Influence of growth regulators EpinTM and Emistym C on the productivity of plantations and fruit quality of strawberry varieties (Fragaria ananassa (Weston) Duсhesne ex Rozier) - А. М. Силаєва; М. М. Спірочкіна (Plant Varieties Studying and Protection)
Purpose. To study the effect of growth regulators EpinTM and Emistym C on yield and quality of strawberry berries of five varieties (Fragaria ananassa (Weston) Duсhesne ex Rozier) with various ripening time. Methods. Field, laboratory, analytical and statistical ones. Results. It was found that there were no impact of growth regulators EpinTM and Emistym C on the speed of phenological phases of strawberry plants development. It was experimentally determined the impact of mentioned substances on the yield of most studied varieties. Laboratory analysis has confirmed the changes in biochemical composition of strawberries. Conclusions. The use of growth regulators EpinTM end Emistym C had a positive effect on fruit yield and quality of studied strawberry varieties. Spraying with these substances increased yields by 14–51% as compared with the control. Content of sugars, dry matter and vitamin C in berries of most of varieties was increasing. At the same time the level of acidity in case of spraying with growth regulators was significantly reducing.